Zooplankton distribution in a mesophotic corals reef habitat at Bajo Frijol seamount, Colombian Caribbean - Laura Contrera Vega; Alejandro Henao Castro; Gabriel R. Navas S (Universitas Scientiarum, 2021)
Mesophotic coral ecosystems (MCEs) shelter unique communities. Coral zooxanthellae in these environments feature a low photosynthesis rate; therefore zooplankton becomes MCEs’ primary food source. These MCEs have not been studied enough due to the high cost of current assessment technologies, so these endeavours remain a challenge. The purpose of this work was to study the zooplankton community associated to the MCEs on seamount Bajo Frijol, within the Corales de Profundidad National Natural Park (off the Colombian Caribbean coast) and to compare its composition with that from shallower parts of the water column. Three samples were taken, filtering 24 L of seawater (via a mesh of size 45 μm) at each station with a device designed to collect zooplankton right on top of the reef substrate. Taxonomic composition, density and relative abundance were obtained. A resemblance analysis was performed, complemented with a cluster, an MDS and a modified Kandoorp test. The analysis showed clear differences between the water column samples from those taken close to the reef. It also showed the separation of the community into two large groups: north and center-south, both with unique species.